Biological aspects of Acacia longifolia, an exotic species potentially invasive in sandy dunes vegetation (Semiárida, 2020)
Coastal dunes in the Southern Pampas are a key habitat for providing ecosystem services and preserving native biodiversity. Acacia longifolia is an exotic tree established at or invading different places in the coast of Argentina. This work describes a stand growing at Monte Hermoso coastal dunes (Buenos Aires province), and evaluates some features of its seeds ecology, including seed size and weight, germination rates and the rate of seed removal by predators. Plant density at the studied population averaged 510 (SE=192.8) individuals/ha, with a canopy cover that reached 42.85% (SE=6.19) and trunk diameters ranging from 6.4 to 14.8 cm. Acacia seeds mean length and width were 3.8±0.07 mm and 2.4±0.04 mm, respectively, with a mean weight of 16.08±0.4 mg. Germination percentages were maximum after chemical and physical scarification of seeds (90±2.98% and 84±5.62%, respectively). The rate of seeds removal reached 27 % (SE=8.3). These results contribute to the knowledge of ecological features of an exotic woody species distributed in pampean grasslands. Their antecedents as an invasive species in similar environments postulate it as a species of risk. In this way, result very important to control the distribution and state, and to avoid the dispersion phase.
Keywords: Coastal dunes; seed ecology; invasive plants; germination; Fabaceae; seed predation